2017
DOI: 10.4095/305838
|View full text |Cite
|
Sign up to set email alerts
|

Setting the stage for multi-spectral acoustic backscatter research

Abstract: The establishment of multibeam echosounders (MBES) as a mainstream tool in ocean mapping has facilitated integrative approaches towards nautical charting, benthic habitat mapping, and seafloor geotechnical surveys. The combined acoustic response of the seabed and the subsurface can vary with MBES operating frequency. At worst, this can make for difficulties in merging results from different mapping systems or mapping campaigns. At best, however, having observations of the same seafloor at different acoustic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…This knowledge is crucial for efforts aiming to increase the discrimination performance. Recent studies have demonstrated that multispectral backscatter data indeed reveal that areas, showing the same acoustic responses for one frequency, differ in the acoustic response of a second frequency (Hughes Clarke, 2015;Brown et al, 2017). This implies that the use of different frequencies might be an appropriate approach to improve seabed sediment classification (Hughes Clarke, 2015) and resolve ambiguities.…”
Section: Current Limitation Of Asc Based On Mbes Backscattermentioning
confidence: 99%
“…This knowledge is crucial for efforts aiming to increase the discrimination performance. Recent studies have demonstrated that multispectral backscatter data indeed reveal that areas, showing the same acoustic responses for one frequency, differ in the acoustic response of a second frequency (Hughes Clarke, 2015;Brown et al, 2017). This implies that the use of different frequencies might be an appropriate approach to improve seabed sediment classification (Hughes Clarke, 2015) and resolve ambiguities.…”
Section: Current Limitation Of Asc Based On Mbes Backscattermentioning
confidence: 99%
“…The cumulative human-induced threats on marine biodiversity and ecosystem goods and services are increasing worldwide while habitat loss and degradation, pollution, overfishing and climate change effects are classified among the most important threats that affect the marine realm [1,2]. Yet, the successful and effective protection and conservation of the marine ecosystem largely depends on our knowledge regarding the spatial extent, the geographical range and the ecological characteristics of the resource or the habitat of interest [3]. Thus, accurate and high-resolution habitat mapping can be considered as a prerequisite in spatial marine management and conservation planning.…”
Section: Introductionmentioning
confidence: 99%
“…This MBES emits a series of signals between 90 and 450 kHz on a ping-by-ping basis. In Brown et al [18], the first multispectral backscatter dataset acquired with a single MBES system (R2Sonic 2026) in the Bedford Basin, Canada, was employed and analyzed. The preliminary results of this study indicate benefits for an improved understanding of seabed characteristics by using multispectral backscatter.…”
Section: Introductionmentioning
confidence: 99%